PLOT SIZE FOR EVALUATION OF AGRONOMIC AND SENSORIAL CHARACTERISTICS OF ARABICA COFFEE - GUARÇONI, Rogério Carvalho; ALIXANDRE, Fabiano Tristão; SOUSA, Douglas Gonzaga; PEREIRA, Lucas Louzada; BRIOSCHI JUNIOR, Dério; SOUSA, Luiz Henrique Bozzi Pimenta de; FAVARATO, Luiz Fernando; MARCATE, João Paulo Pereira (Brazilian Journal of Biometrics, 2020)
Coffee cultivation is of great socioeconomic importance for the Espírito Santo State, generating, in addition to direct and indirect jobs, financial resources. According to the first survey of the 2019 crop of CONAB, it is expected a production between 12.5 to 14.7 million of benefited bags. Research on coffee cultivation has contributed to the development of new technologies, but the size of plots for experiments with coffee is variable and based mostly on the researcher's experience. Thus, the objective of this work was to determine the optimal sizes of experimental plots to evaluate the pre-harvest, production and sensory characteristics of arabica coffee. The modeling applied in this study allows concluding that according to the data tested, it is possible to recommend the optimum size of experimental plots for arabica coffee, for these edaphoclimatic conditions and variety. The conclusions are as follows: it is recommended to use seven or more arabica coffee plants to evaluate the pre-harvest and harvest characteristics (plant height, plant diameter, vigor, and wet mass), and use, at least, seven plants of arabica coffee to evaluate sensory characteristics (fragrance, flavor, aftertaste, acidity, body, uniformity, balance, clean cup, sweetness, overall, and total score).